Sensing and Losing Sense. Dismantling the Domestic - Tomás Errázuriz (ARQ, 2022)
Disassembling a house does not only mean making an inventory of the things we own to fit them into boxes and move them. It also means undoing familiarity with a specific domestic space. By delving into this situation, this text analyzes how the experience of moving deconstructs the everyday life of the domestic and activates our senses around new questions. Ultimately, deconstructing the domestic does not mean destroying it, but rather dismantling it to rethink and reorganize it.